2017
DOI: 10.1093/ageing/afx043
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between depression and executive function and the impact of vascular disease burden in younger and older adults

Abstract: major depression was associated with worse executive function across the lifespan, but minor depression only in younger adults. The impact of vascular burden on the association did not differ between younger and older adults. Therefore, vascular risk reduction is important in both age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…Compatible with our results, in other cross-sectional study, usual WS was associated with executive function on the TMT-B (β = −0.22, p = 0.003) [29]. In addition, a population-based cohort study included 9,402 older adults aged 60 or more had reported that major depression was associated with worse executive function across the lifespan (adjusted for age, gender, and level of education, β = −5.10, p < 0.01) [30].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Compatible with our results, in other cross-sectional study, usual WS was associated with executive function on the TMT-B (β = −0.22, p = 0.003) [29]. In addition, a population-based cohort study included 9,402 older adults aged 60 or more had reported that major depression was associated with worse executive function across the lifespan (adjusted for age, gender, and level of education, β = −5.10, p < 0.01) [30].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Moderate and severe depression has also been associated with EF impairments as well as sleep disturbance. Thus, the unique contribution of sleep quality to EF may be attributed to depression if it is not controlled for in analyses (Lugtenburg et al, 2017).…”
Section: Methodological Differencesmentioning
confidence: 99%
“…1,9,15,[17][18][19]35,36 Another point that it is indispensable to discuss is that both anxiety and depression are risk factors for CVD, such as AMI, stroke, and PAD. 1,15,17,30,[34][35][36][37][38] This could be because patients with anxiety/depression tend to have a less healthy lifestyle, with dietary errors and without physical exercise, 33,39 as was observed in our sample, the great majority of whom did not do regular physical exercise. However, in contrast to some other studies, 33,36 this factor did not affect the presence of depression.…”
Section: Discussionmentioning
confidence: 75%